2001
DOI: 10.1177/109980040100200302
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Hemodynamic Alterations in Canines with Normal Cardiac Function during Exposure to Pressure Support, Continuous Positive Airway Pressure, and a Combination of Pressure Support and Continuous Positive Airway Pressure

Abstract: Variations in intrathoracic pressure generated by different ventilator weaning modes may significantly affect intrathoracic hemodynamics and cardiovascular stability. Although several investigators have attributed cardiovascular alterations during ventilator weaning to augmented sympathetic tone, there is limited investigation of changes in autonomic tone during ventilator weaning. Heart rate variability (HRV), the analysis of beat-to-beat changes in heart rate, is a noninvasive indicator of autonomic tone tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 21 publications
0
36
0
1
Order By: Relevance
“…11,14 Using frequency domain measures of HRV in a group of 6 healthy anesthetized canines with normal ventricular function, Frazier et al 11 found a significant increase in activity of the sympathetic nervous system and a significant decrease in activity of the parasympathetic nervous system with exposure to a combination of pressure support 10 cm H 2 O and continuous positive airway pressure 10 cm H 2 O. In our study, almost half of our patients (49%) had a history of cardiac disease.…”
Section: Mean (Sd)mentioning
confidence: 80%
See 3 more Smart Citations
“…11,14 Using frequency domain measures of HRV in a group of 6 healthy anesthetized canines with normal ventricular function, Frazier et al 11 found a significant increase in activity of the sympathetic nervous system and a significant decrease in activity of the parasympathetic nervous system with exposure to a combination of pressure support 10 cm H 2 O and continuous positive airway pressure 10 cm H 2 O. In our study, almost half of our patients (49%) had a history of cardiac disease.…”
Section: Mean (Sd)mentioning
confidence: 80%
“…during weaning, changes in the ANs with a shift to sympathovagal imbalance (ie, increased sympathetic and/or reduced vagal tone) 11,14 may occur in patients who have underlying cardiovascular dysfunction and impaired compensatory mechanisms, resulting in decreased HRV. [11][12][13][14] sympathetic dominance is associated with decreased duration of myocardial action potential, and increased myocardial excitability, which may enhance abnormal automaticity, triggered activity, and reentry and produce cardiac dysrhythmias.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Not only do deep-sea divers often have difficult tasks to perform, but their body also has to deal with considerable stress caused by this pressurised environment. We can observe this stress, in particular, on the cardiovascular system [1][2][3]: accelerating heart beat due to hypercapnia, impact of pressure variations in the airways on chest venous return, changing myocardial contractile function observed in animal experiments etc.…”
Section: Introductionmentioning
confidence: 99%